Lithium chloride attenuates the abnormal osteogenic/adipogenic differentiation of bone marrow-derived mesenchymal stem cells obtained from rats with steroid-related osteonecrosis by activating the β-catenin pathway - YU, ZEFENG (Int J Mol Med, 2015)
Steroid-related osteonecrosis of the femoral head (ONFH) may be a disease that results from the abnormal osteogenic/adipogenic differentiation of bone marrow-derived mesenchymal stem cells (BMMSCs). In the present study, we examined the possible use of lithium in an aim to reverse the abnormal osteogenic/adipogenic differentiation of BMMSCs isolated from rats with steroid-related ONFH (termed ONFH-BMMSCs). BMMSCs obtained from steroid-related ONFH rat femurs were cultured with or without lithium chloride (LiCl). BMMSCs obtained from normal rat femurs were cultured as controls. LiCl significantly increased the expression of osteocalcin and Runx2 in the ONFH-BMMSCs during osteogenic induction. The mineralization of ONFH-BMMSCs following osteogenic induction was also enhanced. Furthermore, LiCl exerted anti-adipogenic effects on the ONFH-BMMSCs by inhibiting the expression of peroxisome proliferator-activated receptor γ (PPARγ) and fatty acid binding protein 4 (Fabp4) during adipogenic induction, and decreasing lipid droplet formation at the end of adipogenic induction. These effects of LiCl on the ONFH-BMMSCs were associated with an increased expression of β-catenin and a decreased expression of phosphorylated GSK-3β at Tyr-216, and these effects were abolished by treatment with quercetin, an antagonist of the β-catenin pathway. The normal osteogenic/adipogenic activity of BMMSCs may be impaired in steroid-related ONFH. However, as demonstrated by our findings, LiCl reduces abnormal adipogenic activity and simultaneously increases the osteogenic differentiation of ONFH-BMMSCs by activating the β-catenin pathway.